“Someone in Their Corner”: Parental Support in Online Secondary Education - Hanny, Courtney N.; Graham, Charles R.; West, Richard E.; Borup, Jered (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Despite increased interest in K–12 online education, student engagement deficits and the resulting student attrition remain widespread issues. The Academic Communities of Engagement (ACE) framework theorizes that two groups support online student engagement: the personal community of support and the course community of support. However, more evidence is needed to understand how members of these communities, especially parents, support students in various contexts. Using insights gleaned from 14 semi-structured interviews of parents with students enrolled in online secondary school, this study adds support to the roles identified in the ACE framework by presenting real examples of parents supporting their online students’ affective, behavioral, and cognitive engagement. Findings also confirm patterns found in previous research that are not explained using the ACE framework, such as parental advocacy, communication with teachers, and self-teaching. We discuss how a systems approach to conceptualizing the ACE communities allows the framework to more accurately capture parents' perceived experiences within the personal community of support. We also discuss implications for both practitioners and members of students’ support structures.